Newborn infants with bilious vomiting: a national audit of neonatal transport services - Ojha, Shalini; Sand, Laura; Ratnavel, Nanadiran; Kempley, Stephan; Sinha, Ajay; Mohinuddin, Syed; Budge, Helen; Leslie, Andrew (BMJ, 2017)
Objective: The precautionary approach to urgently investigate infants with bilious vomiting has increased the numbers referred to transport teams and tertiary surgical centres. The aim of this national UK audit was to quantify referrals, determine the frequency of surgical diagnoses, with the purpose to inform the consequent inclusion of these referals in the national 'time critical' dataset. Method: A prospective, multi-centre UK-wide audit was conducted (01 August 2015 to 31 October 2015). Term infants, ≤ 7 days of age, referred for transfer due to bilious vomiting were included. Data at the time of transport and outcomes at seven days after transfer were collected by the local teams and tranferred anonymously for analysis. Results: Sixteen teams contributed data on 165 cases. Teams that consider such transfers as “time-critical” responded significantly faster than those that do not classify bilious vomiting as time-critical. There was a surgical diagnosis in 22% cases and 7% had a condition where delayed treatment may have caused bowel loss. Most surgical problems could be predicted by clinical and/or X-ray findings but two infants with normal X-ray features were found to have a surgical problem. Conclusion: The results of this study support the need for infants with bilious vomiting to be investigated for potential surgical pathologies, but the data do not provide evidence for the default designation of such referrals as “time critical.” Decisions should be made by clinical collaboration between the teams and, where appropriate, swift transfer provided.